2019
DOI: 10.1038/s41467-019-11390-8
|View full text |Cite|
|
Sign up to set email alerts
|

Camouflaging bacteria by wrapping with cell membranes

Abstract: Bacteria have been extensively utilized for bioimaging, diagnosis and therapy given their unique characteristics including genetic manipulation, rapid proliferation and disease site targeting specificity. However, clinical translation of bacteria for these applications has been largely restricted by their unavoidable side effects and low treatment efficacies. Engineered bacteria for biomedical applications ideally need to generate only a low inflammatory response, show slow elimination by macrophages, low accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
191
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(226 citation statements)
references
References 46 publications
3
191
0
Order By: Relevance
“…Since genetic programming of bacteria enables them to sense and respond to physiological conditions in situ, this approach is poised to change existing paradigms for diagnosing and treating diseases such as inflammation (12,13), infection (14,15), and cancer (16)(17)(18). An essential element of this approach requires the precise regulation of microbial growth at disease sites, since uncontrolled bacterial replication can lead to severe side effects including tissue damage and septic shock (19,20). Therefore, engineering genetic circuits to control bacterial growth at specific regions provides a promising avenue to address this central challenge in translating next-generation microbial applications.…”
mentioning
confidence: 99%
“…Since genetic programming of bacteria enables them to sense and respond to physiological conditions in situ, this approach is poised to change existing paradigms for diagnosing and treating diseases such as inflammation (12,13), infection (14,15), and cancer (16)(17)(18). An essential element of this approach requires the precise regulation of microbial growth at disease sites, since uncontrolled bacterial replication can lead to severe side effects including tissue damage and septic shock (19,20). Therefore, engineering genetic circuits to control bacterial growth at specific regions provides a promising avenue to address this central challenge in translating next-generation microbial applications.…”
mentioning
confidence: 99%
“…Cargo delivery [120] Cell-membrane-coated bacteria Blood circulation Tumor imaging [121] Cell hybrid Red blood cell-mimicking micromotor Ultrasound energy and magnetotactic control Oxygen transportation [16] Platelet-camouflaged nanorobots Magnetic propulsion and magnetotactic control Isolation of biological threats [124] Macrophage-Mg biohybrid motors Hydrogen bubble propulsion Endotoxin neutralization [125] Neutrophil-based micromotors Cell-driven and chemotactic control Target drug delivery [126] Enzyme-propelled Enzyme-powered microshell motors Catalase-trigged bubble propulsion and chemotactic control, size Drug delivery [141] Mesoporous silica-based nanomotors Urease-powered and pH responsive Target drug delivery [142] Micromotors equipped with DNA nanoswitches Urease-powered and pH responsive Microenvironment sensing and micromotor activity status indicator [143] Ultrasmall stomatocyte motors Biocatalyst catalase and chemotactic control Drug delivery [144] capability through the whole process of performing tasks. Also, the single chemotaxis to the egg cells restricts the potential application of this biohybrid machines.…”
Section: Sperm Hybrid Sperm Cell With Metal-coated Polymer Microhelicesmentioning
confidence: 99%
“…efficacies and unavoidable side effects. Cao et al [121] developed a set of stealth bacteria, cell membrane coated bacteria (CMCB) ( Figure 10D), to eliminate those limitations of earlier developed bacteria hybrid motors such as high accumulation in normal organs, changed inherent bioactivities, and quick clearance by the macrophages. The in vivo results demonstrated that this CMCB was capable to serve as efficient tumor imaging agents and also have the potential for a variety of bacterial-mediated biomedical applications.…”
Section: Bacteria Hybrid Micro/nanomotorsmentioning
confidence: 99%
“…The microbots successfully delivered their cargos of nucleic acid into target cells, which resulted in the subsequent transcription and translation of the target proteins. Moreover, Cao et al used the erythrocyte membrane to coat bacteria to reduce some common side effects associated with live bacterial drug delivery carriers, including high inflammatory response, rapid elimination by macrophages within RES, and low accumulation in target tissues [103].…”
Section: Bacteriamentioning
confidence: 99%